AGE-SPECIFIC CHARACTERISTICS OF PHYSICAL FITNESS OF COLLEGE STUDENTS (Conferencea, 2023)
Periodization of age is conditional to a certain extent and allows to establish approximate boundaries between the phases of its growth, because physical education in each age period has its own different aspects. Age-specific features of the organism determine the content and method of physical training in many aspects, where age-related means are selected, permissible loads and demand standards are determined.